Parental Coping Styles and Its Relationship with the Strengthening Behavior Among Intermediate School Students - Noori, Noor Badri (Al-Adab Journal, 2021)
The current study aims at finding out the correlational relationship between Parental Coping Styles and Its Relationship With the Strengthening Behavior Among Intermediate School Students .In order to achieve this aim , the researcher herself has adopted the Parental Coping Styles Scale by Al-Bazi (2008) .The scale consists of (4) styles ,namely Democratic , Predominating , Excessive Protection , and Negligence Styles .This scale includes two corresponding images , the first is devoted to the father and the second to the mother , containing (25) items distributing into the four styles with four alternatives for responding formulated by Literal Situations Style and Strengthening Behavior Scale by Hameed (2012) which consists of (3) dimensions ,namely the physical , the Literal , and the psychological ones .The scale contains (44) items distributing into the three dimensions of the scale as (12,14,16) and with a grading of Tertiary alternatives (Highly Applicable on me , Somewhat Applicable on me , Never Applicable on me).The researcher has verified the psychometric features of the scale such as Validity and Reliability , then both scales have been conducted on the sample of the study , totally (200) 3rd grade intermediate students of both genders at Directorate General of Education – Al-Karkh Sector /3 -Baghdad during the academic year 2020-2021 .The sample was randomly selected out of the study population.Having collected and statistically analyzed the data, the researcher has come up with the following:-The democratic style is the dominating one , followed by the predominating, and the negligence one , and the excessive protection styles respectively .Also, the sample of the study do not practice the strengthening behavior with their peers and the results show the weak correlational relationship between parental Coping styles (democratic , predominating , excessive protection , and negligence styles) and the strengthening behavior and there is no a statistically significant difference between the two concepts.Based on the above findings, the researcher has set specific recommendations, as well as a number of suggestions for further studies.